Associations between clinical and imaging findings in posterior ankle impingement syndrome: a systematic review. (May 2022) - Baillie, Peta; Mayes, Susan; Lam, Jason; Ferrar, Katia; Cook, Jill
Background: Posterior ankle impingement syndrome (PAIS) is a common and debilitating condition, commonly affecting people who participate in activities that involve repetitive ankle plantarflexion. The relationship between clinical and imaging findings in PAIS has not been established. Purpose: To investigate the relationship between clinical and imaging features in PAIS by reviewing the literature comparing symptomatic patients to asymptomatic controls. Material and Methods: A systematic literature search was performed to identify all English-language articles that compared imaging features in patients diagnosed with PAIS to imaging in an asymptomatic control group. Results: A total of 8394 articles were evaluated by title and abstract, and 156 articles were read in full text. No articles compared imaging findings to an asymptomatic control group, thus no articles met the inclusion criteria. Conclusion: This systematic review found no published research that compared the imaging findings of people diagnosed with PAIS to asymptomatic people. Until this information is available, imaging features in people with posterior ankle impingement should be interpreted with caution.